Analisa Strategi Digital Marketing Adidas dalam Membangun Brand Awareness di Kalangan Generasi Z di Kabupaten Bekasi - Leni Sugiyanti; Yulita Yulita; Ayu Ambarwati; Rendy Permana; Muhammad Daffa Fadhillah (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study analyzes the effectiveness of Adidas’ digital marketing strategy in building brand awareness among Generation Z in Bekasi Regency. The research focuses on how digital initiatives, including social media engagement, interactive content, and online promotional activities, contribute to strengthening consumer recognition and perception of the brand. Adidas utilizes various digital platforms that align with Generation Z’s media consumption patterns, emphasizing visually appealing content, concise messaging, and communication styles that match their preferences. The findings indicate that digital marketing plays a central role in capturing attention, encouraging interaction, and enhancing the overall brand image within this demographic group. Continuous exposure through platforms such as Instagram, TikTok, and online campaigns helps shape a stronger understanding of Adidas’ identity and product values. Moreover, the use of trend-based promotions and relatable digital communication increases emotional connection and encourages positive consumer responses. Overall, the study concludes that Adidas’ digital marketing strategy is effective in elevating brand awareness and reinforcing the brand’s position among young consumers in Bekasi Regency.